Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolates by Conventional Methods and Determination of Their Minimum Inhibitory Concentrations Using VITEK 2: A Prospective Observational Study - Dr. T likhita; Dr. V. Sarojamma; Dr. R. Hymavathi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: MRSA represents a central global contributor to hospital- and community-acquired infections because it produces severe healthcare complications that result in numerous deaths. The main component creating resistance in MRSA is the mecA gene that generates penicillin-binding protein PBP2a/PBP2 through its coding function. Effectual infection control requires immediate identification of MRSA with accurate results to determine proper therapeutic approaches plus prevent spread of multidrug-resistance. Methods: A six-month prospective observational research determined its findings. Biochemical tests identified 314 S. aureus isolates that researchers obtained from different clinical specimens. The testing laboratory performed cefoxitin (30 µg) disc diffusion assays using Mueller–Hinton agar with 2% NaCl enhancement to evaluate all obtained isolates. Additionally they used mannitol salt agar-Ceinasefoxitin (MSA-CFOX) containing 8 mg/L of the antibiotic. VITEK 2 automated system tested the minimum inhibitory concentrations (MIC) values for the identified MRSA isolates after the confirmation step. The lab designation of MRSA required either cefoxitin inhibition zones equal to or less than 21 mm and MIC values at or above 4 µg/mL. Results: Among 314 S. aureus isolates, cefoxitin disc diffusion found 90 cases of MRSA corresponding to 29% of these strains. MSA-CFOX detected 96 potential MRSA isolates based on its results (31%) yet six of these cases turned out to be incorrect due to MIC values which failed to meet the MRSA threshold. The laboratory confirmed 29% of MRSA cases through VITEK 2 testing. The results from cefoxitin disc diffusion tests match closely with VITEK 2 readings which show the validity of disc diffusion testing for MRSA identification but users need to recognize that MSA-CFOX may produce false-positive results in select cases. Conclusion:Definitive MRSA isolate identification uses Cefoxitin disc diffusion together with the VITEK 2 system for accurate MIC value determination in a cost-efficient manner. Therapeutic decision support along with suitable infection control protocols depend on proper identification timing and accurate MIC measurement.